2018
DOI: 10.3748/wjg.v24.i9.992
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy activation by Jiang Zhi Granule protects against metabolic stress-induced hepatocyte injury

Abstract: AIMTo elucidate the potential role of autophagy and the protective effects of Jiang Zhi Granule (JZG) in metabolic stress-induced hepatocyte injury.METHODSAn in vitro and in vivo approach was used in this study. HepG2 cells were incubated in culture medium containing palmitate (PA; 0, 0.1, 0.2, 0.3, 0.4 or 0.5 mmol/L) and treated with or without JZG (100 μg/mL) for 24 h or 48 h, and the progression of autophagy was visualized by stable fluorescence-expressing cell lines LC3 and p62. Western blot analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Hepatocytes were incubated with various concentrations of palmitic acid (PA) as well as in the presence or absence of JZG. Biochemical analyses confirmed the findings of our previous study 21 , in which the levels of alanine aminotransferase (ALT) in the cell supernatants were increased in a dose- and time-dependent manner, and JZG could mitigate the elevated ALT levels (Fig. 1A,B ).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Hepatocytes were incubated with various concentrations of palmitic acid (PA) as well as in the presence or absence of JZG. Biochemical analyses confirmed the findings of our previous study 21 , in which the levels of alanine aminotransferase (ALT) in the cell supernatants were increased in a dose- and time-dependent manner, and JZG could mitigate the elevated ALT levels (Fig. 1A,B ).…”
Section: Resultssupporting
confidence: 89%
“…A great number of signalling pathways have been discovered during the past decade, and we postulated that the mTOR signalling was critically involved in the observed activities of JZG-treated cells. Unlike our previous findings 21 , we confirmed that JZG could inhibit the mTOR activation to up-regulate the IRS-1/PI3K/AKT signalling conversely as well as to activate autophagy. Fluorescence staining with BODIPY and Lyso-Tracker indicated that JZG could promote the co-localization of lipid droplets and lysosomes for degradation, and we also measured the MTP and ROS generation to demonstrate that JZG could protect mitochondrial integrity against oxidative stress.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Nicotinamideadenine dinucleotide phosphate oxidase (NOX) is considered the major cellular ROS source (Loffredo et al, 2016;Long et al, 2017;Rabelo et al, 2018). Its activation has been associated with hepatic injury (Matsumoto et al, 2018;Zheng et al, 2018) and also plays a very plausible role as the starting point of extrahepatic damage, leading to inflammation and fibrosis through activation of Kupffer cells and hepatic stellate cells (HSCs) (Das et al, 2015;, thus causing a self-perpetuating circle of ROS formation and ROS-mediated damage (Masarone et al, 2018;Zhong and Liu, 2018). Therefore, NOX-specific antioxidant therapies may be a promising intervention to prevent or to treat NASH.…”
mentioning
confidence: 99%